Good Governance Pada Penerapan Aplikasi Tangerang Live di Kota Tangerang - Putri, Putri Ariviani Safitri; Ralita Ayu Pratiwi; Nida Aeni; Rika; Widiana Astuti Simamora; Yunizar Fazriyanti; Risma Ramahyanti (JURNAL SOSIAL Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Good Governance is generally defined as the proper management of government based oncertain rules and fundamental principles. A "good" government in this context refers to one that adheresto the core principles of Good Governance, namely participation, rule of law, transparency, responsiveness,consensus orientation, equity, effectiveness and efficiency, accountability, strategic vision, and mutualopenness. Tangerang Live is a digital platform specifically created for the residents of Tangerang City withthe aim of enhancing their quality of life and overall welfare. This application offers various features suchas up-to-date information, public services, and interactive features that facilitate communication betweenthe public and the local government. The purpose of this study is to examine whether the implementationof the Tangerang Live application aligns with the principles of Good Governance. The research methodused is a literature review (library research) by collecting data and information from theoretical literature,e-journals, and relevant books related to the topic of study. The results indicate that the implementation ofthe Tangerang Live application in improving public services in Tangerang City has generally beensuccessful and reflects several principles of Good Governance. However, there are still a number ofchallenges that need to be addressed to ensure the platform's optimal and sustainable performance.